Characteristics of Pulmonary Tuberculosis Patients Based on Age, Gender, and Education in the Pondidaha Public Health Center - Tosepu, Ramadhan; Rafid, Abd.; ., SriWulan; ., Machmud; ., Usman; ., Nurlela (KnE Social Sciences, 2023)
According to the World Health Organization (WHO), tuberculosis (TB) is a global public health emergency because tuberculosis is widespread and difficult to treat. The researchers in this study tried to segment the tuberculosis sufferers in the Pondidaha Health Center service area based on age, gender, and level of education. Workplace analysis was carried out at the Pondiha Health Center. There were 35 subjects. SPSS was the analysis software used. According to the results of this study, age is not the main risk factor for tuberculosis. There was no relationship between a lower education level and an increased risk of tuberculosis. Gender does not play a significant role in the development of tuberculosis. Keywords: Age, Education, Gender, Pulmonary Tuberculosis